Metamirrors Based on Arrays of Silicon Nanowires with Height Gradients. Issue 4 (27th January 2017) - Otte, Marinus A.; Garcia‐Martin, Antonio; Borrise, Xavier; Sepulveda, Borja
Abstract : Arrays of silicon nanowires with height gradients fabricated using metal‐assisted chemical etching act as tunable metamirrors enabling light focusing the reflected light in arbitrary shapes. Metamirrors with non‐cylindrical nanowires can simultaneously focus the reflected light and induce strong polarization conversion effect.